Studi Komparatif Tahanan Gesek antara Tiang Terpancang dan Tiang Tertimbun pada Tanah Pasir Pantai - I Made Dirgayusa; Sito Ismanti; Ahmad Rifa’i (Jurnal Aplikasi Teknik Sipil, 2025)
The position of foundation pile caps of monument constructed on coastline changed from below to above the soil surface. Therefore, the piles were driven in a free-standing condition and then covered with beach sand soil. This research aims to analyze the frictional resistance of buried pile, then compare it with the frictional resistance of ordinary piles. Practical analysis methods and finite element methods using RS Pile software are compared to obtain a representative method. The comparison results show that the Meyerhof method has the closest soil bearing capacity behavior to the field test results. Based on the results, the skin friction of buried piles is 52% - 57% lower than ordinary piles. This decrease occurred because the assumed value of the angle of friction in the soil was lower because the soil around the pile was not as dense as in ordinary conditions which compacted during the driving process.